The History of Social Exclusion and Moral Condemnation of Prostitution - Teodoro, Maria Cecília Máximo (2015)
From a detailed historical account, this article aims to demonstrate the history of social exclusion and moral condemnation of prostitution. It was decided to address the prostitution of women, given that this genre that makes up the vast majority of workers in this activity. It will address the prostitution activity since its inception while divinity in his wake stereotyped by the Bible, until we reached the twenty-first century and verify the conditions under which their work is performed and judged. Although this activity is considered a profession, as part of the Brazilian Code of Occupations and has social security contribution of code, the historical record presented here brings up a historical reality exclusions in the past and present, alerting, so for a necessary cultural change, social, moral and mainly legal in the sense of giving dignity to these women.